Methodological aspects of the conjugated execution of manoeuvres in the high-speed application of defensive and counter-attacking actions - Kan, L.V.; Zakharova, Yu.V.; Chudakov, A.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the methodological aspects of the conjugated execution of manoeuvres in the high-speed application of defensive and counter-attacking actions. Results and conclusions. The main stages of preparation for the formation of skills of conjugated execution of manoeuvres in the high-speed application of defensive and counter-attacking actions are identified. The main components of tactical interaction, sensorimotor corrections of motor actions in the training process are examined, for the automation of movement during switches from one action to another.